Quarter Life Crisis dengan Turnover Intention Karyawan Fresh Graduate Generasi Z Kota Semarang - Gabriel Angela Sutanto; Sutarto Wijono (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Quarter life crisis is a psychological condition commonly experienced by individuals in early adulthood and can influence career-related decisions, including increasing the tendency toward turnover intention. This study aims to examine the relationship between quarter life crisis and turnover intention among Generation Z fresh graduate employees in Semarang City. A quantitative approach with a correlational design was employed, involving 274 respondents aged 22–27 years, holding a Diploma or Bachelor’s degree, with 1–2 years of work experience, and residing in Semarang City. The instruments used were the Quarter Life Crisis Scale (QLCS) and the Expressed Turnover Intention Scale. The analysis revealed a positive and significant correlation between quarter life crisis and turnover intention, with a correlation coefficient of r = .563 (p < .05). These findings indicate that the higher the level of quarter life crisis, the higher the turnover intention. The implications of this study highlight the importance of addressing the psychological well-being of Generation Z fresh graduates to reduce turnover intention.